Countermeasure development for Rift Valley fever: deletion, modification or targeting of major virulence factor NSs - Lihoradova, Olga (2014)
Rift Valley fever (RVF) is a mosquito-borne zoonotic disease characterized by a high rate of abortion in ruminants, and febrile illness, hemorrhagic fever, retinitis and encephalitis in humans. RVF is caused by the RVF virus (RVFV), belonging to the genus Phlebovirus of the family Bunyaviridae. RVFV encodes a major virulence factor, NSs, which is dispensable for viral replication, yet required for evasion of host innate immune responses. RVFV NSs inhibits host gene upregulation at the transcriptional level, while promoting viral translation in the cytoplasm. In this article, we summarize the virology and pathology of RVF, and countermeasure development for RVF, with emphasis on NSs function and applications.